2015
DOI: 10.1016/j.ergon.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorder prevalence and psychosocial risk exposures by age and gender in a cohort of office based employees in two academic institutions

Abstract: This study presents data on self-reported prevalence of Musculo Skeletal Disorder (MSD) symptoms and psychosocial risk exposures by age and gender among a group of office based University workers who use their computers for at least 25% of their work day. Employees in two academic organisations received an invitation to participate in an on-line questionnaire. A total of n=852 office workers participated in this study; yet respondents who were employed for greater than 12 months were only included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 38 publications
7
61
1
1
Order By: Relevance
“…Often there are differences between the job tasks and roles of male and female workers; these differences may account for differential exposure to risk factors for MSD symptoms development (Widanarko et al, 2011;Hooftman et al, 2009;Collins and O'Sullivan, 2015;Calvet et al, 2012). Women are more likely to report work-related symptoms regardless of body region (Hirata, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Often there are differences between the job tasks and roles of male and female workers; these differences may account for differential exposure to risk factors for MSD symptoms development (Widanarko et al, 2011;Hooftman et al, 2009;Collins and O'Sullivan, 2015;Calvet et al, 2012). Women are more likely to report work-related symptoms regardless of body region (Hirata, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…This is in line with the theory [12] that there is no maximum capacity index on static activity; muscle strength is therefore not related to MSD complaints. In addition, with respect to the age factor, a previous study [13] found that there was no association between age and MSD complaints. In this study, 70 percent of the respondents were 24-40 years old and therefore still productive.…”
Section: Resultsmentioning
confidence: 99%
“…The NMQ is widely used to assess selfreported MSD symptoms (Widanarko et al, 2011;Collins and O'Sullivan, 2015). The first part of the questionnaire contained questions relating to demographic features: age, height, weight, hand dominance and years of practice.…”
Section: Questionnaires and Data Collectionmentioning
confidence: 99%